2009
DOI: 10.1080/01411590903471564
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sintering temperature on phase-formation behavior and mechanical properties of silica ceramics prepared from rice husk ash

Abstract: Silica ceramics were prepared using three types of raw materials derived from rice husk. Cleaned husk and acid-leached husk were burned at 700 C to get brown ash (BA) and white ash, respectively. The third type was silica gel (SG) derived from BA through the alkaline extraction of silica from ash followed by acid neutralization. Granulated powders were pressed and pellets were sintered at 700-1400 C range. Phase-formation behavior, densification characteristics, and mechanical strength of ceramics were investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 27 publications
4
18
0
1
Order By: Relevance
“…4(b), a crystalline structure was observed after sintering up to 900°C. This result is consistent with the findings of Nayak and Bera 35) who reported in 2009 that amorphous silica of WRHA transforms into crystalline form (depending on the impurities present in the ash) upon heat treatment in the temperature range of 9001300°C. Figure 4(b) shows that the two forms of crystalline silica were cristobalite and tridymite and that the predominant phase was cristobalite.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…4(b), a crystalline structure was observed after sintering up to 900°C. This result is consistent with the findings of Nayak and Bera 35) who reported in 2009 that amorphous silica of WRHA transforms into crystalline form (depending on the impurities present in the ash) upon heat treatment in the temperature range of 9001300°C. Figure 4(b) shows that the two forms of crystalline silica were cristobalite and tridymite and that the predominant phase was cristobalite.…”
Section: Resultssupporting
confidence: 82%
“…2(a) shows, the relationship between the density and porosity is not linear. The same nonlinearity was reported by Haslinawati et al and by Nayak et al, 34), 35) who noted that the density increases with decreasing pore content and increasing sintering temperature. Figure 4 shows the results of the XRD analyses of the three samples (S 1 , S 2 and S 3 ) at 1200°C [ Fig.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…aush/autumn rice) and stored for 1-2 years in farmers' ambient seed storage would constitute a worthwhile study. A study of seed deterioration vis-à-vis the seed's potential for cell protection during post harvest aging under ambient (including UV) environment is particularly relevant for rice seed since rice husk is composed of 80%-90% compound of amorphous silica, Nayak and Bera, (2009) that is UV transparent, Hsiang et al, (2001) and allows high penetration of UV into rice seed. Tosserams et al, (1997) have demonstrated reduction in germination and seedling performance in S.jaobaea seeds under enhanced ambient UV-B radiation during April in dune grassland ecosystem, Netherlands.…”
Section: Introductionmentioning
confidence: 99%
“…8 After that, the RH was treated at different temperatures that were 550 C, 600 C, 700 C and 800 C to establish the suitable temperature that can obtain an elevated amount of SiO 2 by reduction of the carbonaceous materials present inside the samples. 9 The RHA samples were analyzed by using XRF measurement to achieve the element and oxide percentage composition within the samples.…”
Section: Rice Husk Compositionsmentioning
confidence: 99%